KETENTUAN PUASA BAGI WANITA HAMIL DAN MENYUSUI - RIRIN FAUZIYAH (UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI, 2021)
Pregnant and breastfeeding women are one of the groups affected by the chitab of the fasting order as mentioned in surah al-Baqarah (02) verse 183. However, in the following verse, verse 184 of surah al-Baqarah (02) it is explained that for people who are sick or on the way (then not fasting), it is obligatory to change (qadha') fasting for as many days as the day left. Meanwhile, people who are hard to fast are obliged to pay fidyah. This difference of opinion is motivated by the view that pregnant and breastfeeding women are legally equal with menstruating women, childbirth, sick people and travelers. So that only obliged to replace the fast (qadha’) the fast only. While some other scholars view that pregnant and breastfeeding women cannot be the same as those who are sick but are equated with people who are hard to fast so that apart from being obliged to change their fast (qadha’), their fasting is also required to pay fidyah. This difference of opinion results in confusion in the community, especially for pregnant and breastfeeding women who are unable to carry out the Ramadan fast regarding the obligation to replace the fast (qadha’) the fast that was left alone or replace the fast (qadha’) fasting and pay fidyah.